EVALUATION OF VILLAGE INFRASTRUCTURE DEVELOPMENT POLICY IN LIMAU SUNDAI VILLAGE, AIR PUTIH DISTRICT, BATU BARA REGENCY - Fitra Sirait; Jhon Simon; Kariaman Sinaga (Universitas Dharmawangsa Medan, 2026)
Abstract Village infrastructure development is a strategic instrument to improve community welfare and to strengthen development equity in rural areas. This study aims to evaluate the implementation of village infrastructure development policies in Limau Sundai Village, Air Putih Sub-district, Batu Bara Regency. The evaluation focuses on planning and implementation processes, community participation, supporting and inhibiting factors, as well as policy outcomes and impacts on socio-economic conditions. A qualitative descriptive method was applied. Data were collected through in-depth interviews, participatory observation, and document study. The informants comprised village officials, the Village Consultative Body (BPD), the Activity Implementation Team (TPK), community leaders, and beneficiary residents. The data were analysed using the interactive model of Miles and Huberman, while the policy evaluation framework drew on William N. Dunn's six evaluation criteria and George C. Edwards III's policy implementation model. The findings indicate that the village infrastructure policy has been carried out in accordance with formal village procedures and has improved accessibility, mobility, and local economic activity. Several challenges remain. These include the limited technical capacity of implementers, the suboptimal community participation in monitoring and maintenance, and inequitable benefit distribution across hamlets. The study concludes that strengthening transparency, meaningful participation, quality control, and sustainable maintenance arrangements is essential to enhance the long-term effectiveness of village infrastructure policies. Keywords: Policy Evaluation; Village Infrastructure Development; Village Fund; Community Participation; Public Welfare